O strategiach grzecznościowych polskich i niemieckich studentów na przykładzie reakcji na komplementy - Frankowska, Violetta (Investigationes Linguisticae, 2010)
This article presents the complimenting behaviour of German and Polish students: strategies they use when respoding to compliments. The speech act was also analysed as regards the concept of face and positive and negative politeness. A corpus of 345 German and Polish compliment responses was examinated. The results show the existence of cross-cultural differences as well as similarities between the two groups of students. The article presents parts of author’s Master’s Thesis.